2013
DOI: 10.1167/iovs.11-9310
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Atrophy of Retinal Ganglion Cells Precedes theBax-Dependent Stage of Apoptosis

Abstract: Retinal ganglion cell somas and nuclei undergo the AVD in response to optic nerve damage. Atrophy is rapid and precedes the Bax-dependent committed step of the intrinsic apoptotic pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(62 citation statements)
references
References 65 publications
6
56
0
Order By: Relevance
“…Blocking these latter changes results in substantial cell survival that diminishes over time and modest or no regeneration (2,3,7,9,10). Subsequent changes include down-regulation of IGF1 and phospho-Akt, increases in reactive oxygen species, the unfolded protein response and endoplasmic reticulum stress, caspase activation, histone deacetylation, gene silencing, diminished intracellular cAMP, and changes in levels of anti-and proapoptotic Bcl-like proteins (4)(5)(6)8). Although the mechanistic relationships between Zn 2+ dysregulation and these other changes remains to be investigated, the observations that Zn 2+ chelation diminishes several hallmarks of RGC death (caspase 3 activation, CHOP expression, Bcl-xL down-regulation), affords long-term survival for many RGCs, and stabilizes the high but transient neuroprotective effects of pten deletion (Fig.…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…Blocking these latter changes results in substantial cell survival that diminishes over time and modest or no regeneration (2,3,7,9,10). Subsequent changes include down-regulation of IGF1 and phospho-Akt, increases in reactive oxygen species, the unfolded protein response and endoplasmic reticulum stress, caspase activation, histone deacetylation, gene silencing, diminished intracellular cAMP, and changes in levels of anti-and proapoptotic Bcl-like proteins (4)(5)(6)8). Although the mechanistic relationships between Zn 2+ dysregulation and these other changes remains to be investigated, the observations that Zn 2+ chelation diminishes several hallmarks of RGC death (caspase 3 activation, CHOP expression, Bcl-xL down-regulation), affords long-term survival for many RGCs, and stabilizes the high but transient neuroprotective effects of pten deletion (Fig.…”
Section: +mentioning
confidence: 99%
“…Under normal circumstances, retinal ganglion cells (RGCs), the projection neurons of the eye, cannot regenerate axons after the optic nerve has been damaged and soon undergo cell death, leaving victims of traumatic or ischemic nerve injury or degenerative conditions, such as glaucoma, with permanent visual losses. Optic nerve injury leads to numerous pathological changes in RGCs and reversing some of these changes improves cell survival, although these effects are often transitory and for the most part promote little or no axon regeneration (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). Regeneration per se can be induced by intraocular inflammation combined with elevated cAMP (11,12), counteracting cell-intrinsic (13)(14)(15) or cellextrinsic (16,17) suppressors of axon growth, oncomodulin and other growth factors (18)(19)(20)(21)(22), or elevated physiological activity (23,24).…”
mentioning
confidence: 99%
“…20 The dendritic arbor field radius and the number of branches decrease in size, 29,67 and the RGC soma and nucleus shrink. 34 Ultimately, BAX-dependent intrinsic apoptosis is activated in the soma and allows for systematic destruction of the critically injured neuron and removal from the retinal environment. 18,34,68 While these degenerative events are predictable in models of glaucoma, an interesting characteristic is that they do not occur synchronously: they are compartmentalized.…”
Section: Glaucomatous Neurodegeneration Is Compartmentalizedmentioning
confidence: 99%
“…In addition to culture work that allows for the functional study of retinal cell types, animal models have been developed in zebrafish, 14 pigs, 15 mice, [16][17][18][19][20][21] rats, 9,[22][23][24][25] rabbits, [26][27][28] and nonhuman primates [28][29][30] using a variety of surgical techniques to mimic glaucomatous neuropathy. Most commonly used are procedures to elevate IOP by laser-induced trabeculoplasty to create ocular hypertension, 7,9,31 the induction of RGC degeneration and death through optic nerve trauma by transection 22,30,32,33 or crush, 17,23,[34][35][36] and animal models that spontaneously develop high IOP accompanied by RGC injury and loss. 6,19,29 Animal models are especially important when studying the complexity of the retinal environment, which is an intricate network of neuronal and support cells that is difficult to replicate in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the displaced amacrine cells account for the majority of non-RGCs in the GCL of mice [1,41]. Among the displaced amacrine cells in the GCL, starburst amacrine cell is the predominant type and has the average soma diameter about 8 µm, while the soma diameters of RGCs vary from 12 to 18 µm [41][42][43][44]. Given the fact that the mean nuclear size of the measured RGCs (8.8 ± 1.6 µm) is similar to the mean soma size of the amacrine cells (i.e.…”
Section: Imaging Of Rgcs and Nerve Fibers In The Nfl And Gclmentioning
confidence: 99%